2008
DOI: 10.1021/bc800066b
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase-Catalyzed Synthesis of a Universal Coil-Chitosan Bioconjugate for Protein Immobilization

Abstract: Chitosan has been reported as a promising material for gene and drug delivery as well as for tissue engineering and regenerative medicine. We report here the conjugation of a de novo designed coil peptide (Kcoil) to chitosan ( M(n) = 200 kDa) to achieve a universal Kcoil-chitosan scaffold for subsequent immobilization of proteins tagged with the Kcoil partner, i.e., the Ecoil peptide. Kcoil-chitosan conjugate was synthesized using a tyrosinase-catalyzed protocol. Extensive UV/vis and IR characterization demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…To reduce cost associated with enzymes, various techniques have been developed to enable their repeated use in multiple rounds of processing. To render them reusable, enzymes have been immobilized on solid matrices [2][3][4] such as sepharose [5], polyester [6], chitosan [7], magnetic affinity sorbent [8] and carbon nanotubes [9], either via covalent attachment or adsorption. However, biocatalysts in solid-liquid interfaces are often accompanied by a reduced activity as the accessibility of the enzymes to the substrate is potentially limited.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce cost associated with enzymes, various techniques have been developed to enable their repeated use in multiple rounds of processing. To render them reusable, enzymes have been immobilized on solid matrices [2][3][4] such as sepharose [5], polyester [6], chitosan [7], magnetic affinity sorbent [8] and carbon nanotubes [9], either via covalent attachment or adsorption. However, biocatalysts in solid-liquid interfaces are often accompanied by a reduced activity as the accessibility of the enzymes to the substrate is potentially limited.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a tyrosinase-catalyzed oxidation-grafting reaction has been used by [29] for the conjugation of de novo designed coil peptides, called Kcoil and Ecoil, that heterodimerize in a highly specific and stable fashion to adopt a coiled-coil structure, characterized by the repetition (five times in each peptide) of K-V-S-A-L-K-E and E-V-S-A-L-E-K heptads, respectively. Demolliens et al [29] studied the conjugation of the Ecoil/Kcoil system with chitosan to obtain a scaffold or particles for subsequent immobilization of proteins tagged with the Ecoil peptide.…”
Section: Tyrosinase In Biomedical Applicationsmentioning
confidence: 99%
“…Demolliens et al [29] studied the conjugation of the Ecoil/Kcoil system with chitosan to obtain a scaffold or particles for subsequent immobilization of proteins tagged with the Ecoil peptide. Precisely, the system Kcoil/chitosan has been found to be able to recruit the Ecoiltagged epidermal growth factor (EGF) via coiled-coil interactions.…”
Section: Tyrosinase In Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan, a cationic polysaccharide with abundant amines has been largely studied as its attractive properties including excellent film-forming ability, good biocompatibility and adhesion. However, it is reported that chitosan film may block the electron transfer between electrode and target molecules because of its electroinactivity [19,20]. In this paper, gold-chitosan nanocomposites with the adsorption of chitosan molecules on particle surfaces was prepared which obtained the better electron transfer ability than pure chitosan and better stability than pure gold nanoparticles as chitosan is very effective stabilizing agent for gold nanoparticles.…”
Section: Introductionmentioning
confidence: 99%